Using Role Play to Improve EFL Learners’ Self-Confidence in Oral Performance : The Case of First-year Students at Laghouat University - Korichi, Souhila; Guesmia, Ikrame; Korichi, Souhila (University ofAmmar Theledji -Laghouat, 2022)
Algerian universities have some challenges in improving oral and communicative skills for EFL learners. Due to the complexity of the speaking skills, our learners find it hard to master all its aspects and use them appropriately in different social contexts. It has been noticed that learners’ difficulties in expressing their ideas in theEnglish language can be attributed to their lack of self-confidence. Therefore, this research attempts to investigate the use of Role Play as a technique to improve EFL learners’ Self-Confidence. The present study aims at shedding light on improving learners’ Self-Confidence through the Role Play technique to promote learners’ oral skills. Accordingly, we hypothesize that using Role Play activities in EFL classrooms would make first-year students of English at Laghouat University interested to inspeaking English and communicating effectively in different social situations. The descriptive method is adopted; it consists of administering a questionnaire to first- year LMD students in oral classes at Amar Telidji University of Laghouat to investigate their attitudes towards using Role Play to develop their Self-Confidence and enhance their oral performance. Results from the analysis of the questionnaire have shown that the use of theRole Play technique helps to improve learners’ Self-Confidence as well as their oral and communicative skills to speak the English language easily. At the end of this research, we recommend that teachers should encourage students to use role-play with the aim of making them interact in real life situations and the ministry of education should support such techniques to overcome the learners’ psychological difficulties that can harm their educational career.